The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2196/19847
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Medical Students on the COVID-19 Pandemic: Survey of Nine Medical Schools in Uganda

Abstract: Background The coronavirus disease (COVID-19) pandemic is a global public health concern affecting over 5 million people and posing a great burden on health care systems worldwide. Objective The aim of this study is to determine the knowledge, attitude, and practices of medical students in Uganda on the COVID-19 pandemic. Methods We conducted an online, descriptive cross-sectional study in mid-April 2020, us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
81
12
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(169 citation statements)
references
References 17 publications
37
81
12
21
Order By: Relevance
“…Previous research works have either unveiled the KAP of general public or investigated the mind set of isolated groups (students, doctors, patients, etc.) preferentially [1,7,8] . The information available so far is piecemeal which cannot be construed into a meaningful representation of the wholesome health care team.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research works have either unveiled the KAP of general public or investigated the mind set of isolated groups (students, doctors, patients, etc.) preferentially [1,7,8] . The information available so far is piecemeal which cannot be construed into a meaningful representation of the wholesome health care team.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study 78.4% of participants knew about the signs and symptoms of COVID-19, which is lesser compared to a study from India, in which 86.7% of participants were aware of these symptoms and from Uganda, where 95% of students were aware of it. [22,23] In the present study 99.3% of participants were aware about the important protective measures like avoiding crowds and maintaining hand hygiene. This is also in accordance to a study from India, where 96.9% of participants knew about preventive measures.…”
Section: Resultsmentioning
confidence: 50%
“…The KAP (knowledge, attitudes, and practice) studies conducted in different medical schools across the world have revealed for example that >80% of Jordanian medical students have adequate knowledge about the pandemic and are adopting correct practices during this period. 35 A further survey in Ugandan medical students revealed that 91% had good knowledge about the pandemic, 74% a positive attitude, 57% good practices, and 80% of students were ready to volunteer in frontline care, 36 while 96.6% of medical students at an Indian medical school reported practicing increased hand-washing during the pandemic, 92.7% had appropriate knowledge of COVID-19, and >80% had a positive attitude toward COVID-19. 37 Another study reported inadequate knowledge and practices in healthcare workers, including medical undergraduates, in India.…”
Section: Discussionmentioning
confidence: 99%